The Etiology, Assessment and Treatment of Compulsive Checking: A Review - Guo S; Yadegar M; Khaw H; Chang S (Psychology Research and Behavior Management, 2025)
Sisi Guo, Mina Yadegar, Helen Khaw, Susanna Chang UCLA Semel Institute for Neuroscience and Human Behavior, Los Angeles, CA, USACorrespondence: Sisi Guo, Email sisiguo@mednet.ucla.eduAbstract: Checking is the most reported compulsion of Obsessive-Compulsive Disorder (OCD), impacting 80% of individuals with the psychiatric condition. In this narrative review, we describe the theoretical conceptualization and empirical research of compulsive checking to highlight advancements and limitations in our current understanding of OCD. In terms of etiology, research shows that anxiety, uncertainty and inflated responsibility elicit checking, which in turn negatively impact memory confidence and higher-level cognitive functions. In addition, compulsive checking is linked to altered neural activities in the brain’s subcortical regions. Although these studies have their methodological limitations, they collectively highlight the behavioral, cognitive and neurobiological underpinnings of OCD. In terms of assessment of compulsions such as checking, there is a suite of empirically validated tools that range from standardized diagnostic interviews to self-report measures. Recent innovations also include experimental and technology-assisted assessment tools. Finally, in terms of treatment, Exposure and Response Prevention (ERP) is the most empirically supported intervention for OCD that is supported by habituation and inhibitory learning models. There is preliminary support for cognitive therapy to target specific symptoms such as compulsive checking. However, more rigorous testing is warranted to determine its efficacy and mechanism of change.Keywords: checking, OCD, exposure and response prevention, neurobiological, cognitive behavioral